Монетное обращение золотоордынского города Маджар - Лебедев, В.П.; Павленко, В.М. (Степи Европы в эпоху средневековья, 2008)
Majar, one of the largest towns of the Golden Horde, was located on the left bank of the middle Kuma river. The written sources contain no information about the time of its foundation whereas its destruction is connected with the capture of the town by Timur’s troops in 1395. Sporadic studies of different degree of preservation of Majar ruins located on the territory of modern Budyonnovsk town and its outskirts have been conducted for 3 centuries. However, the results of these investigations are much more modest than those of ancient hillforts of other Golden Horde towns of the same status, such as Bulghar, Saray, and Gulistan. The paper is targeted at detailed studying of one of the most important sides of a medieval town life, i.e. its monetary circulation.